Historical Factors of Long-Term Economic Growth and Declination in Argentina: An analysis of the 20th Century - Dabús, Carlos Darío (2023)
This paper explores the historical long-term determinants of economic growth in Argentina along the XX century. The evidence indicates that at the beginning economic openness plays a key role to explain the successful performance achieved until the great crisis of 1930. From there on, and until the middle of the ́70s, Argentina maintained a similar growth of the previous period, which was driven by the domestic demand via investment. Nonetheless, in the last quarter of the past century economic growth slowed drastically, which was mainly associated with economic instability, approx-imated by infl ation and the per capita growth rate output volatility. The intuition is that once the country lost foreign markets for its exports, could temporarily sustain growth thanks to domestic demand, but once this strat-egy petered out the economy was signed by a long period of turbulence and stagnation, specifi cally since 1975 onwards. Thus, economic policy recom-mendations are to develop new led export-oriented sectors, so that alleviate the external restriction, as to avoid procyclical policies in order to reduce the economic instability.